Developing a Comprehensive Higher Education Service Quality Model in Ethiopian Context - Zelalem Zekarias Oliso; Demoze Degefa Alemu; Jonathan David Jansen; Jeilu Oumer Hussein (International Journal of Educational Management and Development Studies, 2023)
The existing literature lacks a comprehensive service quality model to measure higher education service quality, particularly from the Ethiopian higher education context. The main purpose of this study was to address this literature gap. To serve the study purpose, the existing generic service quality models mainly designed for market and higher education sectors were thoroughly reviewed. Through an extensive literature review, a comprehensive higher education service quality model was developed. The content validity and reliability of the instrument were empirically tested in three public universities representing 30% of universities located in the Southern part of Ethiopia. Five experienced experts who were selected from three different sample universities judged the content validation of the instrument. The experts’ judgment in each item was quantitatively calculated using the Content Validity Index. The pilot study was conducted on 40 regular undergraduate students who were purposively selected from the different University departments to further analyze the reliability of the instrument while the internal consistency of the instrument was checked at Cronbach’s alpha coefficient of 0.5 using Statistical Package for Social Sciences v.20. The findings of the study revealed that the newly developed model was valid and internally consistent. Since the present model is comprehensive and empirically tested in the Ethiopian higher education context, the model better measures the Ethiopian higher education service quality. However, further studies should be conducted using Exploratory Factor Analysis (EFA) to strengthen the present findings.